2019
DOI: 10.2478/bjmg-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the JAK2V617F mutational burden in patients with philadelphia chromosome negative myeloproliferative neoplasms: A single-center experience

Abstract: The identification of the JAK2V617F mutation in several distinct myeloproliferative neoplasms (MPNs) raised the question how one single mutation incites expression of at least three different clinical phenotypes, i.e., polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF). In order to further evaluate already published data on the correlation between mutant JAK2V617F allele burden and specific hematological and clinical parameters, we tested the level of the JAK2 mutation in 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In our study, ET patients with high mutation loads of >50% showed lower hemoglobin levels, in line with some studies yet in contrast with most previous data [ 5 , 7 , 8 , 27 , 28 ]. In agreement with some previous studies but contrary to some others [ 4 , 5 , 7 , 8 , 27 , 28 ], we found no association with high mutation load or leukocyte count. We observed a trend towards lower platelet counts in ET patients with high mutation loads in line with the report published by Pich et al [ 27 ] yet contrary to most previous data.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, ET patients with high mutation loads of >50% showed lower hemoglobin levels, in line with some studies yet in contrast with most previous data [ 5 , 7 , 8 , 27 , 28 ]. In agreement with some previous studies but contrary to some others [ 4 , 5 , 7 , 8 , 27 , 28 ], we found no association with high mutation load or leukocyte count. We observed a trend towards lower platelet counts in ET patients with high mutation loads in line with the report published by Pich et al [ 27 ] yet contrary to most previous data.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies proposed different cut-off values for JAK2V617F allele load for the stratification of ET cases [ 2 , 4 , 5 , 7 , 8 , 24 , 25 , 26 , 27 , 28 ]. In our study, ET patients with high mutation loads of >50% showed lower hemoglobin levels, in line with some studies yet in contrast with most previous data [ 5 , 7 , 8 , 27 , 28 ]. In agreement with some previous studies but contrary to some others [ 4 , 5 , 7 , 8 , 27 , 28 ], we found no association with high mutation load or leukocyte count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable level of JAK2 kinase activity as a reflection of the relative proportion of mutated and wild-type protein in the cell was one of them which gained much attention [19]. The concept of gene dosage postulates a counterpart between clinical manifestations and the proportion of JAK2V617F mutant alleles with the term 'allele burden' addressing the ratio of mutant and wild type JAK2 alleles in cells [24].…”
Section: Jak2v617f Allele Burdenmentioning
confidence: 99%
“…Multiple studies have shown a substantial differences of allele burden in different MPN phenotypes [19], [25]. In the majority of cases, the lowest allele burden was recorded in ET and higher allele burden in PV [24], [25], with PMF patients recording varied results [27]. An allele burden greater than 50% was observed to increase the probability of an overt PV or myelofibrotic evolution [28].…”
Section: Jak2 Allele Burden and Phenotypementioning
confidence: 99%